2018
DOI: 10.1590/1516-3180.2018.0005240418
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported assessment of female sexual function among Brazilian undergraduate healthcare students: a cross-sectional study (survey)

Abstract: Sexual dysfunction was identified in at least a quarter of these young undergraduate women and it was not associated with gynecological problems, menstrual cycles, dysmenorrhea, contraceptive use or physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
3
3
0
2
Order By: Relevance
“…This also points out the significance of FSD among different populations and cultures and goes to support the validity, consistency and reliability of the FSFI tool and its variants. This was similar to other studies in higher income countries such as among German female medical students (40.0%) by Wallweiner et al 13 and among female students (42.3%) of the University of Texas by Chapa et al 26 Nevertheless, a study carried out among Brazilian students by Satake et al 26 showed that the prevalence of FSD was lower at 28.8%. This could be attributed to the documented lesser risk of FSD in Hispanic women compared to women of other races such as women of African descent.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This also points out the significance of FSD among different populations and cultures and goes to support the validity, consistency and reliability of the FSFI tool and its variants. This was similar to other studies in higher income countries such as among German female medical students (40.0%) by Wallweiner et al 13 and among female students (42.3%) of the University of Texas by Chapa et al 26 Nevertheless, a study carried out among Brazilian students by Satake et al 26 showed that the prevalence of FSD was lower at 28.8%. This could be attributed to the documented lesser risk of FSD in Hispanic women compared to women of other races such as women of African descent.…”
Section: Discussionsupporting
confidence: 90%
“…Being unmarried but in a relationship was the sole independent factor associated with a lower risk of having FSD. This was also seen in other studies done in other tertiary institutions by Escajadillo-Vargas et al 24 and Satake et al 26 This could be as a result of the increased emotional satisfaction which comes with being in a relationship. 29,30 Furthermore, being in a lower educational level was seen to be related to having a higher risk of FSD compared to those in the higher levels.…”
Section: Discussionsupporting
confidence: 77%
“…Which seems to be not more than SD reported in other women in Iran [ 29 – 31 ]. The women’s SD reported in other countries is approximately similar to our findings: 25.6% of Chinese women [ 32 ] and 28.8% of Brazilian women [ 33 ] except women’s SD reported in Polish women (16. 2%) [ 34 ] that is lower than our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Outro fator relacionado à disfunção sexual identificado no estudo foi a ausência de parceiro fixo. Para alguns autores, a presença de um parceiro fixo reduz as chances de disfunção sexual feminina devido à segurança que o relacionamento proporciona à mulher, pois ela tem mais intimidade com seu corpo e de seu parceiro, consegue quebrar tabus morais, e desempenha sua sexualidade de forma satisfatória 34,37,38 .…”
Section: Discussionunclassified
“…Distúrbios de excitação, lubrificação, orgasmo, satisfação e dor são domínios que afetam a sexualidade feminina e provocam a disfunção sexual, dentre os quais se destacam os distúrbios de orgasmo e desejo 30,37,38,47 . Esses distúrbios associam-se à comunicação deficiente com o parceiro, ausência de preliminares e religião.…”
Section: Discussionunclassified